Telecommunications and business strategy [ - Gershon, Richard A. (Telecommunications (Mahwah, N.J.), 2009)
Telecommunications and Business Strategey helps current and future media professionals understand the relationship and convergence patterns between the broadcast, cable television, telephony, and Internet communication industries. Author Richard A. Gershon examines telecommunications industry structures and the management practices and business strategies affecting the delivery of information and entertainment services to consumers. He brings in specialists to present the finer points of management and planning responsibilities. Case studies from the International Radio and Televisi